Sistem Informasi Data Siswa Pada Sekolah Dasar Negeri 042 Bengkulu Utara Menggunakan PHP Dan MYSQL - Setiaji Ayu Handayani; Khairil Khairil; Venny Novita Sari (UNIVED Press, 2025)
Rapid developments in information technology have encouraged many educational institutions to implement digital systems for data management. SDN 042 North Bengkulu previously used Microsoft Excel to record student data, but this method was inefficient and prone to errors, especially with the increasing number of students. The purpose of this study was to create a web-based information system using PHP and MySQL, which is expected to improve efficiency, accuracy, and security in student data management. The method used in developing the system was the waterfall method, with stages of requirements analysis, system design, code writing, testing, and implementation and maintenance. The result of this research is a student data information system developed for SD N 042 North Bengkulu that successfully meets the school's administrative needs effectively. This system facilitates online recording, searching, and reporting of student data. Because it is web-based, this system can be accessed at any time from various devices and is proven to be more practical than the previous manual method